Support for Balanced Juvenile Justice: Assessing Views About Youth, Rehabilitation, and Punishment - Mears, Daniel P. (Journal of quantitative criminology, 2015)
Objectives The juvenile court was envisioned as a system of justice that would rehabilitate and punish young offenders. However, studies have not directly measured or examined support for “balanced” juvenile justice—that is, support for simultaneously employing juvenile rehabilitation and punishment to sanction youth—or how beliefs central to the creation of the court influence support for balanced justice. Drawing on scholarship on juvenile justice and theoretical accounts of views about sanctioning, the study tests hypotheses about such support. Methods The study employs multinomial logistic regression, using data from 866 college students enrolled in criminology and criminal justice classes, to examine support for different approaches to sanctioning violent juvenile offenders. Results Analyses indicate that a majority of respondents supported balanced justice for violent delinquents, approximately one-third supported a primarily rehabilitation-focused approach to sanctioning, and the remainder supported a primarily punishment-oriented approach. Individuals who believed that youth could be reformed and deserved treatment were more likely to support balanced justice or a primarily rehabilitation-oriented approach to sanctioning youth. Conclusions The findings underscore the nuanced nature of public views about sanctioning youth, the salience of philosophical beliefs to support different sanctioning approaches, and the importance of research that accounts for beliefs central to the juvenile court’s mission.